A serious game to prevent bullying and promote empathy - Raminhos, Cátia; Claúdio, A. P.; Carmo, M. B.; Carvalhosa, S.; Candeias, M.; Gaspar, A. (10th Iberian Conference on Information Systems and Technologies, CISTI 2015, 2015)
Bullying is a real and serious problem with severe consequences for the young victims of this phenomenon. Serious Games have proven their effectiveness in therapeutic approaches to problems within the Conflict Resolution domain, thereby revealing a potential to be explored in the mitigation of peer violence in and outside the school. This paper presents a Serious Game whose main goal is to promote empathy as a mean to prevent bullying; the rationale for the prevention is that by helping victims and observers of these episodes of violence to practice an attitude/behavior change toward bullying one will be training and increasing those attitudes and behavioral competences for the real bullying situations. The relevance of our proposal is based on the high prevalence of bullying and the lack of demonstrated effectiveness of the current prevention interventions. The game runs on different platforms (smartphone, tablet, PC), provides flexibility in the choice of scenarios and in the game playing role. Player's decisions have obvious effects in the subsequent levels of the game. The treatment or intervention resorting to this game may take place at the therapist's office or outside, in an independent way. In every game session a data set is recorded for later analysis by the therapist. We also implemented a Back Office application integrated with the game to support the therapist in several monitoring tasks.